Boiogito extract alters fecal bile acid profile in mice: Possible roles in changes in fecal and liver lipid levels. Issue 3 (29th July 2020) - Chen, Zhuoer; Watanabe, Shiro; Nishidono, Yuto; Tanaka, Ken
Abstract : Aim: Boiogito (BOT) extract is reported to improve hepatic lipid states in the experimental conditions of fatty liver. We hypothesize that the effects of BOT extract may involve alterations of hepatic and intestinal bile acids. The aim of this study is to examine whether BOT extract alters the levels of bile acids and lipids in the liver and feces using mice. Methods: Mice were fed a diet with or without BOT extract for five weeks and feces and liver were harvested for the determination of bile acids, cholesterol and triacylglycerols (TAGs). Results: BOT extract administration did not change the profile of hepatic bile acids but decreased the hydrophobicity and level of deoxycholic acid (DCA), a potent farnesoid X receptor (FXR) agonist, in fecal bile acids. BOT extract increased the fecal excretion of cholesterol but decreased that of non‐esterified fatty acids (NEFAs). BOT extract did not change the fecal excretion of TAGs. BOT extract decreased the levels of cholesteryl esters (CEs) and TAGs in the liver. Conclusion: Our data suggest that BOT extract might increase fecal cholesterol excretion and decrease hepatic lipid levels by decreasing the hydrophobicity and level of an FXR agonist in intestinal bile acids.